Skateboarding and the changing city: lessons from the public spaces of Reykjavik - Inkster, Colton (2015)
Skateboarding has become a world-wide phenomenon that has the ability to fit into any culture. Iceland supports a healthy, vibrant skateboard culture. The city itself is young and undergoing many changes presently that have both positive and negative effects on the skateboard community. These redevelopment projects have an impact on the skateboarders' identities because they are formed out of occupied spaces. Qualitative methods such as participant observation were used to explore Reykjavik's skateboard culture. Understanding how skateboarders feel about public spaces can help in understanding how these spaces can be used to improve the city. Some of the most important skatespots in Reykjavik are Ingolfstorg and Harpa, both of which are part of redevelopment projects. Having access to this type of high quality public space has provided a setting for the development of a healthy skateboard community. May 2015